Two-part onboarding for game-based learning environments - Vidaković, Milan; Lara, Macarena; Duchi, Lorenzo; Whitcomb, Alexander; Paas, Fred (Frontiers in Education, 2023)
The trend of introducing game-based elements and mechanisms via game-based learning (GBL) and gamification is expanding in higher education, as is research on the elements of gamification design that contribute to their effects on learning. This paper presents a two-part onboarding process as a game-design element, analyzing its underlying mechanisms and potential effects on student learning through theoretical frameworks. First, we introduce a two-part onboarding intervention designed as part of introducing GBL in higher education. The intervention aims to address a challenge students face when taking a GBL module or course: namely, that venturing into a new digital platform often brings with it new and unfamiliar expectations of how students should act and interact in order to effectively engage with the course material as well as with their peers and instructors. Second, we describe two projects through which the intervention evolved to its current form. Third, we analyze and apply two theoretical frameworks-on semiotic domains and cognitive load-to examine the underlying mechanisms by which the intervention may be expected to affect student learning.